Răspunsuri la criza ocupării. Transformări digitale ale pieței muncii din România - Delia Bădoi; Ana Maria Preoteasa (Sociologie Românească, 2024)
The present article presents a sociological analysis of the sources of crisis in the context of the Romanian labour market, compared to post-socialist and post-Soviet countries. The study examines the labour market changes over the past two decades, from the economic crisis of 2008 to the COVID-19 crisis. The article shows how socioeconomic vulnerabilities during crises interacted with the transformations caused by employment policies, technological transformations of work and neoliberal measures on the labour market in Romania.